On the search for nucleation agents in BaO-SrO-ZnO-SiO2 glasses: The influence of P2O5. Issue 4 (April 2018) - Thieme, Katrin; Zscheckel, Tilman; Thieme, Christian; Höche, Thomas; Rüssel, Christian
Abstract: Glasses in the system BaO-SrO-ZnO-SiO2 from which a phase with the composition Ba1-x Srx Zn2 Si2 O7 can be precipitated possess a strong tendency towards surface crystallization and due to the high anisotropy of the coefficient of thermal expansion of this crystal phase, the obtained glass ceramics often show microcracking. The present article deals with the effect of P2 O5 on the crystallization behavior of BaO-SrO-ZnO-SiO2 glasses. The phase formation and the microstructure of the glass ceramics are studied using thermal analyses, X-ray diffraction, optical microscopy, as well as scanning electron microscopy. While the stoichiometric glass melt spontaneously crystallizes upon cooling, the P2 O5 addition leads to a stabilization of the glass enabling the preparation of a glass without any crystals. The appearance of stresses and microcracks during crystallization can be assigned to certain crystallographic directions using electron backscatter diffraction. Moreover, it is possible to achieve volume crystallization in this otherwise solely surface crystallizing glass system.